If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 35t = 50t + -37.5 Reorder the terms: 35t = -37.5 + 50t Solving 35t = -37.5 + 50t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-50t' to each side of the equation. 35t + -50t = -37.5 + 50t + -50t Combine like terms: 35t + -50t = -15t -15t = -37.5 + 50t + -50t Combine like terms: 50t + -50t = 0 -15t = -37.5 + 0 -15t = -37.5 Divide each side by '-15'. t = 2.5 Simplifying t = 2.5
| (6xy^2-xy)(6xy^2+xy)= | | 4(y+1)=-6 | | x^2-2x+10=y | | 5x+2x-5=44 | | 7t^3-21t^2-2926t=0 | | 9+5x=4x+12 | | -4+5w=-14 | | 8x+9x-52=104-9x | | -(x-8)=3(-3x+4) | | 8=Xsquared-5x+8 | | 120+30m=80+50m | | 5-x=18+3x | | 4+2.5x=6.5x+2 | | -1+3-x=4+2x | | 28.75=6g+3.97 | | -6(2n-1)=-66 | | a+4+4a=14 | | 2g+16=2g+28 | | 8g=4+10g | | 1/2+(2/3+3/4)-4/5*5/6= | | 3(v+8)-5v=6 | | .25x+9.99=113.74 | | 5(y-1)=2(y-4)-6 | | 9y-6x=3+5x | | 7s-(3s+1)=4(s+s) | | -2(n-5)+4n=17 | | -(-x+w)-2(-4w+5x)= | | F(x)=4x+10F(2) | | sqrt(3x+1)-sqrt(x-1)=2 | | 4a+3=7a-16 | | 80=11c+32 | | 1/2+(2/3/3/4)-4/5*5/6= |